(untitled) (Journal of the College of Basic Education, 2022)
The arts are one of the most important aspects of ancient civilizations, and these arts have had the greatest merit in showing the social, religious, economic and political values ​​of societies, in addition to the aesthetic taste that distinguished them. Through the artistic eras produced by civilizations, we can extrapolate what these societies thought, their way of life, and their view of existence, and it is not hidden that each society has its own civilized activity.